Effects of Alkali Stress on the Growth and Menaquinone-7 Metabolism of Bacillus subtilis natto - Chen, Xiaoqian; Shang, Chao; Zhang, Huimin; Sun, Cuicui; Zhang, Guofang; Liu, Libo; Li, Chun; Li, Aili; Du, Peng (Frontiers in Microbiology, 2022)
Menaquinone-7 (MK-7) is an important vitamin K2, synthesized from the menaquinone parent ring and seven isoprene side chains. Presently, the synthesis of MK-7 stimulated by environmental stress primarily focuses on oxygen stress, while the effect of alkali stress is rarely studied. Therefore, this study researched the effects of alkali stress on the fermentation performance and gene expression of Bacillus subtilis natto. The organism’s growth characteristics, biomass, sporogenesis, MK-7 biosynthesis, and gene expression were analyzed. After a pH 8.5 stress adaptation treatment for 0.5 h and subsequent fermentation at pH 8.5, the yield of MK-7 increased to 2.10 times. Transcriptomic analysis showed that the MK-7 high-yielding strain had enhanced carbon source utilization, increased glycerol and pyruvate metabolism, enhanced the Embden-Meyerhof pathway (EMP), tricarboxylic acid (TCA) circulation flux, and terpenoid biosynthesis pathway, and promoted the accumulation of acetyl-CoA, the side-chain precursor of isoprene. At the same time, the up-regulation of transketolase increased the metabolic flux of the pentose phosphate (HMP) pathway, which was conducive to the accumulation of D-erythrose 4-phosphate, the precursor of the menadione parent ring. This study’s results contribute to a better understanding of the effects of environmental stress on MK-7 fermentation by Bacillus subtilis natto and the molecular regulatory mechanism of MK-7 biosynthesis.